The Role of the Islamic Study Groups in Medan City in Creating and Fostering Sakinah Families - Syukri Syukri; Sulaiman Muhammad Amir (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The Majelis Taklim (Islamic study groups) play a strategic role in building and fostering harmonious families in Medan. In the challenging context of modern life, families face various social and moral issues that can disrupt household harmony. Therefore, family development through religious education provided by Majelis Taklim is crucial. This study aims to analyze the role of Majelis Taklim in realizing and fostering harmonious families in Medan. This study used a qualitative method with a descriptive approach. Data were obtained through interviews, observations, and documentation of several Majelis Taklim (Islamic study groups) in Medan. The results indicate that Majelis Taklim plays a role in increasing religious understanding, strengthening moral values within the family, and building household harmony through Islamic studies, spiritual guidance, and family mentoring. In conclusion, Majelis Taklim is a crucial institution in fostering harmonious families by providing ongoing religious education and building awareness of the importance of Islamic values in family life.